UJI GETARAN SEISMIK PADA RANCANG BANGUN REAL TIME SEISMIC MEASUREMENT (RSAM) MENGGUNAKAN FAST FOURIER TRANSFORM (FFT) - Umi Salamah (Navigation Physics : Journal of Physics Education, 2020)
Indonesia is one of  the countries with the most volcanoes in the world. Observation, monitoring, recording, dissemination of information and warning of danger signs for volcanic activity is one of the focuses in the response to volcanic disasters. The instrument used to monitor volcanic activity is Real-time Siesmic Amplitude Measurement (RSAM). RSAM is a system that provides a continuous measurement of the seismic amplitude of the absolute average of the number of seismic stations. RSAM occupies a strategic role in monitoring volcanic seismic activity, especially in times of crisis before the eruption. In this study designing RSAM systems using geophone sensors to detect seismic vibrations. System testing is done by varying the test frequency. The test frequency given starts from 10 Hz to 50 Hz. The results of this study indicate that a system that has been designed to build can detect vibration signals well. This is evidenced by the Fast Fourier Transform (FFT) spectrum which shows the suitability of the test frequency with the spectrum peak produced.